(untitled) (Research, Society and Development, 2022)
Biological nitrogen fixation (BNF) performed by diazotrophic bacteria is a natural process and contributes to the economic viability and sustainability of the production system. In this sense, the present work aimed to characterize growth-promoting bacteria in eucalyptus, as well as their interaction with nitrogen doses in the initial development of eucalyptus seedlings. The bacterial strains used in the experiment were JM2R, JN5R, JN6R and LG2F. The experiment was carried out in pots with a capacity of 20L, with a randomized block design (DBC), consisting of 3 replications and a 5x4 double factorial, where the first factor was composed of the isolates and a control, and the second factor was nitrogen levels. (0, 25, 50 and 70 kg ha-1). The parameters evaluated were height, number of shoots, shoot dry mass and root dry mass. The interaction of factors was significant, and for height and shoot dry mass, the dose of 70 kg ha-1 provided the highest means.